Gerakan #MeToo dalam Mempromosikan Kesetaraan Buruh: Komparasi Indonesia dan Korea Selatan - Natasya Ramadhani Prasetyo (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2023)
Gender equality is something that is still being fought for by feminist activists in various countries. This article discusses the gender gap experienced by female workers in Indonesia and South Korea. #MeToo as a transnational feminist movement can be a catalyst for creating gender equality in various countries. Many #MeToo activists say that this movement can symbolize women workers whose voices are never heard. This study uses qualitative methods to describe phenomena and analyze them in depth. The results of the study found that the #MeToo movement has promoted labor equality, both in Indonesia and in South Korea. However, in terms of legislation, it still has no impact on making laws that can protect women workers from discrimination from companies. This is due to the strong patriarchal culture in both countries so that discrimination in wages and treatment is only seen as a condition that must be accepted.